Pengaruh Pemberian Leguminosa Indigofera sebagai pengganti Konsentrat dalam Ransum Kambing PE terhadap Kualitas Susu, Produksi dan Kecernaan Zat Makanan - Mhd. Taufiq Hadi Wijaya; Mardiati Zain; Elihasridas Elihasridas (Universitas Batanghari Jambi, 2023)
This study aims to obtain the results of concentrate substitution by administering Leguminosa indigofera zollingeriana with treatment (10%, 20%, 30%) in the ration on milk quality, milk production, consumption and digestibility of nutrients in PE goats. The experiment was carried out using a randomized block design (RBD) with 4 treatments with 4 replications. These treatments include: Treatment A is field grass 60%: 40% concentrate; Treatment B is 60% field grass: 30% concentrate + 10% I.zollingeriana; Treatment C was 60% field grass: 20% concentrate + 20% I.zollingeriana; Treatment D was 60% field grass: 10% concentrate + 30% I.zollingeriana. Parameters observed were milk quality, production and digestibility of nutrients. The results of the analysis showed that the use of leguminosa indigofera zollingeriana as a substitute for concentrate had no significant effect (P>0.05) on the quality and production of milk and the digestibility of nutrients. The best results were in treatment D with 60% field grass: 10% concentrate + 30% I.zollingeriana.